2017
DOI: 10.1177/0333102417722521
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of strength training on tension-type headache: A randomised controlled study

Abstract: Background Strength training has shown effects in reducing neck pain. As neck pain is highly prevalent in tension-type headache (TTH), it is relevant to examine the effect of strength training of the shoulder muscles on TTH patients. Aim To examine the effect of strength training of the shoulder/neck muscles on TTH frequency and duration. Methods Sixty patients with TTH were randomised into strength training or a control group. The strength training group trained ten weeks with elastic resistance bands. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 34 publications
0
42
0
10
Order By: Relevance
“…20 It was aimed to include 60 TTH patients and 30 healthy controls based on power calculations for the primary outcome in the intervention part of the study (frequency and duration presented previously). 13 , 22 After the baseline case–control testing, the healthy controls exited the trial. In the RCT, the TTH patients were randomized by a random sequence generator into two groups, and the patients were not blinded to allocation.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…20 It was aimed to include 60 TTH patients and 30 healthy controls based on power calculations for the primary outcome in the intervention part of the study (frequency and duration presented previously). 13 , 22 After the baseline case–control testing, the healthy controls exited the trial. In the RCT, the TTH patients were randomized by a random sequence generator into two groups, and the patients were not blinded to allocation.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Previously, similar analysis on the primary outcomes, headache frequency and duration has been published. 13 , 22 Further medication intake was registered as a secondary outcome, and it has been analyzed and published that no significant reduction after intervention was found. 22 In addition, it was shown that there were patients with coexisting migraine and and these showed a similar decrease in force as those with only TTH.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In einer zweiten kleinen Studie wurde dieses Krafttraining mit einer Verbesserung der ergonomischen Arbeitsplatzgestaltung verglichen. Beide Interventionsgruppen zeigten eine Verbesserung bezüglich ihrer Kopfschmerzen ohne signifikanten Unterschied zwischen den Gruppen [44].…”
Section: Krafttrainingunclassified